A Study on Basic Health And Safety Knowledge That Influence The Safety At Maritime‘A Case Study Of DD & I Engineering Sdn. Bhd. / Irwan Ibrahim...[et al.] - Ibrahim, Irwan; Md Esa, Mashitah; Othman, Hasbullah; Bohiran, Irnaema (2010)
Safety must be considered for all level of employee. The human life depends and responsible on the safety level at work place. Any safety issues are crucial to all established company.This study was conduct in DD & I Engineering Sdn. Bhd., a subcontractor company for Malaysia Marine and Heavy Engineering Sdn. Bhd. (MMHE), which deals with the heavy work focusing on maritime. The company located at Pasir Gudang, Johor and established since 2001. The core business of the company are constructions with its core competencies in marine engineering that include blasting, painting, hydro jetting, power tooling, cleaning, mucking-out sludge, dislodging, disloping, valve, piping, main engines services, boiler, generator, cooling system, pump, navigation, underwater works and repair, maintenance and services of all kind of works pertaining of marine, ship and vessel. This study is to identify the relationship between health and safety knowledge towards the safety at maritime. The researcher chooses five basic health and safety knowledge as independent variable which are fire, manual handling, noise and vibration, safety signs and general health and safety. The questionnaires were distributed to the respondent as a method of data collection. These knowledge generally will influence the safety performance at maritime, but through the survey that have been conducted, it have the different result from the expectation. At the end of this study, the researcher recommends several recommendation in order to improve the safety performance at maritime. Hopefully, this study can be the guideline to maintain the safety level at work place.